Analisis Perbedaan dan Daya Terima Saus Lo Mein Instan Dengan Penggunaan 3 Jenis Pati Berbeda Sebagai Rintisan Usaha - Fidiyani Aryo Wicaksono; Destarasta Amurwa Bhumi; Muhammad Iqbal Ramadhan; Yeni Yulianti; Guspri Devi Artanti (Journal of Innovative and Creativity (Joecy), 2026)
This study aimed to analyze the sensory quality of instant Lo Mein sauce using three types of natural starches, namely corn starch, cassava starch, and arrowroot starch, to evaluate consumer acceptance of the best formulation, and to develop the product as a business start-up. The research was conducted at the Pastry and Bakery Laboratory, Applied Culinary Arts and Food Service Management Study Program, Faculty of Engineering, Universitas Negeri Jakarta. The study employed an experimental method consisting of three stages: sensory quality evaluation by 10 expert panelists, consumer acceptance testing involving 100 consumer panelists, and business start-up development. The evaluated attributes included color, aroma, taste, texture, and overall product quality. The results showed that the type of starch significantly affected the sensory quality of the instant Lo Mein sauce. Based on the expert panelists' evaluation, cassava starch produced the best sensory characteristics and subsequently achieved the highest level of consumer acceptance in terms of color, aroma, taste, texture, and overall quality. The best formulation was then developed into an instant Lo Mein sauce product under the brand name Me!nova, marketed in a 250 ml spout pouch package at a selling price of IDR 20,000 per package. During one sales period, the Me!nova product generated a total revenue of IDR 600,000,-. The instant Lo Mein sauce product is expected to promote the utilization of local food resources and create new business opportunities within the community